2017
DOI: 10.1016/j.jfda.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different partitioned solvents on chemical composition and bioavailability of Sasa quelpaertensis Nakai leaf extract

Abstract: The leaves of Sasa quelpaertensis Nakai were extracted with 80% ethanol and further partitioned with n-hexane, chloroform, ethyl acetate, n-butanol, and aqueous fractions to evaluate the biological activity through assessment via various in vitro assays, including total phenol content; 1,1-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis-(3-ethylbenzothiazothiazoline-6-sulfornic acid (ABTS) radical scavenging; reducing power; α-glucosidase and tyrosinase inhibitory; and alcohol dehydrogenase (ADH) and aldehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
9
26
0
1
Order By: Relevance
“…Their presence in polar fractions could perhaps explain why polar solvents, such as water and alcohol, are used in indigenous medicine to macerate or prepare most herbal formulations. This finding is in congruent with the result of other studies (Faraone et al, ; Nakamura, Ra, Jee, & Kim, ). Phenolic compounds, which includes flavonoids, are known to exhibit antioxidant activities and are soluble in polar solvents such as alcohol and acetone (Luo, Basile, & Kennelly, ).…”
Section: Discussionsupporting
confidence: 94%
“…Their presence in polar fractions could perhaps explain why polar solvents, such as water and alcohol, are used in indigenous medicine to macerate or prepare most herbal formulations. This finding is in congruent with the result of other studies (Faraone et al, ; Nakamura, Ra, Jee, & Kim, ). Phenolic compounds, which includes flavonoids, are known to exhibit antioxidant activities and are soluble in polar solvents such as alcohol and acetone (Luo, Basile, & Kennelly, ).…”
Section: Discussionsupporting
confidence: 94%
“…Extract yield of Gleditsia triacanthos L pods prepared by maceration using increasing polarity solvents showed that the polar extracts (crude methanolic extract, n-butanol and aqueous fractions), were found to contain the highest yields. This result was in full agreements with other studies 7,19,21,22 . The yield is a relative parameter and depends on the plant species studied, the part used in the extraction, the drying and storage conditions, the content of each species in secondary metabolites and the nature of the solvent used in the plant extraction as well as the extraction method itself.…”
Section: Total Antioxidant Capacitysupporting
confidence: 93%
“…Therefore, this study was designed to investigate the effect of oral SQE on the ovariectomized rats with repeated stress and to explore its mechanisms that exhibited the antidepressant-like effect. We intended to administer two different doses of SQE (100 and 300 mg/kg) since SQE chemical composition and bioavailability are well studied in these two doses [28]. Our present data demonstrated that continuous administration of the SQE orally for 2 weeks induced an antidepressant-like effect on the ovariectomized rat with repeated stress.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, this bamboo grass gained more attention in traditional medicine due to its dietary phytochemicals (including p-coumaric acid and tricin) that boost general health [27][28][29][30][31][32]. It is reported that bamboo leaf extract enhanced the levels of acetylcholine and -aminobutyric acid (GABA) in rat's hippocampus and improved the learning and memory ability of dementia model rats [33].…”
Section: Introductionmentioning
confidence: 99%